Non-noble metal-based molecular complexes for CO2 reduction: From the ligand design perspective. Issue 3 (June 2020) - Liu, Dong-Cheng; Zhong, Di-Chang; Lu, Tong-Bu
Highlight: Non-noble metal based molecular complexes for CO2 reduction have been reviewed from the ligand design perspective. The relationship between catalytic performance and ligand structure has been discussed and concluded. Constructive suggestions in designing efficient molecular catalysts for CO2 reduction have been put forward. Abstract: Molecular catalysts for electrochemical and photochemical CO2 reduction have developed rapidly during the past two decades. Using non-noble metal (Ni, Co, Mn, Fe, and Cu) complexes as molecular catalyst, numerous catalytic systems have shown good catalytic performance for CO2 reduction. It is useful to draw conclusions from the results of reported works and identify concepts that may provide future frameworks in catalyst design for CO2 reduction. It is well-known that the ligand in molecular complexes is one of the key factors affecting catalytic performance. Modification of the ligand structure has become an important strategy to improve the catalytic performance. This review, beginning with a brief general introduction to molecular catalysis of CO2 reduction, intends to reveal ligand effects of non-noble metal complexes on the catalytic performance for CO2 reduction. The latest progress on both electrocatalytic and photocatalytic CO2 reduction by non-noble metal complexes has been summarized, wherein, emphasis has been placed on the effect of ligands on catalyst efficiency, selectivity and stability. New developments involving immobilization of non-noble metal complexes on solid supports or electrodes have also been discussed. Finally, several constructive suggestions in designing efficient molecular catalysts for CO2 reduction have been put forward. Graphical abstract: Image, graphical abstract